2016
DOI: 10.1038/srep25905
|View full text |Cite
|
Sign up to set email alerts
|

Branched Peptide, B2088, Disrupts the Supramolecular Organization of Lipopolysaccharides and Sensitizes the Gram-negative Bacteria

Abstract: Dissecting the complexities of branched peptide-lipopolysaccharides (LPS) interactions provide rationale for the development of non-cytotoxic antibiotic adjuvants. Using various biophysical methods, we show that the branched peptide, B2088, binds to lipid A and disrupts the supramolecular organization of LPS. The disruption of outer membrane in an intact bacterium was demonstrated by fluorescence spectroscopy and checkerboard assays, the latter confirming strong to moderate synergism between B2088 and various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 62 publications
3
35
0
Order By: Relevance
“…The incubation of Mygalin with LPS caused a reduction in the absorbance as a function of the increase in the LPS concentration, indicating an interaction between the molecules. Similar results were described with peptides incubated with LPS (Lakshminarayanan et al, 2016;Sinha et al, 2017). Our data suggest that Mygalin may interact FIGURE 6 | Escherichia coli filamentation assay as indicative of DNA inhibition by Mygalin.…”
Section: Interaction Of Mygalin With Lpssupporting
confidence: 84%
See 2 more Smart Citations
“…The incubation of Mygalin with LPS caused a reduction in the absorbance as a function of the increase in the LPS concentration, indicating an interaction between the molecules. Similar results were described with peptides incubated with LPS (Lakshminarayanan et al, 2016;Sinha et al, 2017). Our data suggest that Mygalin may interact FIGURE 6 | Escherichia coli filamentation assay as indicative of DNA inhibition by Mygalin.…”
Section: Interaction Of Mygalin With Lpssupporting
confidence: 84%
“…The possible interaction of Mygalin with LPS showed that there was an interaction between these two molecules, partially explaining its action against Gram-negative bacteria. Other drugs, such as curcumin and antimicrobial peptides, have the same ability to interact with LPS, reducing their activity (Lakshminarayanan et al, 2016;Sinha et al, 2017). The presence of chelating metals can interfere with E. coli metabolism, leading to its death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods include the time-consuming mutation based empirical method, statistically based bioinformatics methods, and more sophisticated mechanism based methods such as MD simulations and biophysical experiments. Recently, multi-disciplinary approaches combining computational predictions, biophysical characterizations and biological validations have proved to be more promising (Bai et al, 2012 ; Koh et al, 2015a ; Lakshminarayanan et al, 2016 ). This section discusses various experimental and computational methods that have been used for AMP design.…”
Section: Methods For Amp Designmentioning
confidence: 99%
“…Obligate anaerobes and facultative anaerobes are the primary pathogens that cause pulpitis (4). Following lysis, Gram-negative bacteria release bacterial endotoxin, which has strong cytotoxicity and antigenicity (5). Endotoxin may directly destroy the local tissues and induce an inflammatory reaction (6).…”
Section: Introductionmentioning
confidence: 99%